THE INFLUENCE OF COMPETENCE, LOYALTY AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE THROUGH WORK ENVIRONMENT AS INVERVENING VARIABLES IN PT PROPERNAS GRIYA UTAMA - Ismail, Wahyu Adi; Rusdianti, Endang; Utaminingsih, Adijati (Sekolah tinggi ilmu ekonomi pemuda, 2023)
The problem that occurred at PT. Propernas Griya Utama is a decline in employee performance from 2019 to 2021. There are still previous research results which have led to research gaps. The results of these previous studies show different findings - differences in the effect of competence, loyalty, job satisfaction on performance. This makes researchers use the work environment as an intervening variable to overcome research gaps. This research is causal (cause - effect). Data analysis uses structural equation modeling (SEM) to find solutions from the structural model. Test using Partial Least Square (PLS). Based on the research that has been completed, the results conclude that employee performance is directly influenced by competence, loyalty, job satisfaction and work environment. Besides that, this study produced the work environment as an intervening variable with indirect effect. Based on the research that has been completed, the results conclude that employee performance is directly influenced by competence, loyalty, job satisfaction and work environment. Besides that, this study produced the work environment as an intervening variable with indirect effect. Based on the research that has been completed, the results conclude that employee performance is directly influenced by competence, loyalty, job satisfaction and work environment. Besides that, this study produced the work environment as an intervening variable with indirect effect. Keywords: Competence, Loyalty, Satisfaction, Environment, Performance.